Efficient Ammonia Electrosynthesis and Energy Conversion through a Zn‐Nitrate Battery by Iron Doping Engineered Nickel Phosphide Catalyst. Issue 13 (9th February 2022) - Zhang, Rong; Guo, Ying; Zhang, Shaoce; Chen, Dong; Zhao, Yuwei; Huang, Zhaodong; Ma, Longtao; Li, Pei; Yang, Qi; Liang, Guojin; Zhi, Chunyi
Abstract: The electrocatalytic nitrate reduction reaction (NO3 ‐RR) to ammonia (NH3 ) offers a promising alternative approach for NH3 production and nitrate‐based voltaic cells which can deliver both electricity and NH3 as products, are also highly attractive. However, nitrate‐to‐NH3 conversion involves a proton‐assisted multiple‐electron transfer process with considerable kinetic barrier, underlying the need for efficient catalysts for the NO3 – RR. A Zn‐nitrate battery is reported to enable a "killing three birds with one stone" strategy for energy supply, ammonia production and removal of pollutants with the iron doped nickel phosphide (Fe/Ni2 P) as a NO3 – RR catalyst electrode. Iron doping induces a downshift of the d‐band center of Ni atoms to the Fermi level, allowing the optimization of Gibbs free energies for reaction intermediates. The Fe/Ni2 P catalyst exhibits 94.3% NH3 Faradaic efficiency (FE) and nearly 100% nitrate conversion efficiency at –0.4 V vs. reversible hydrogen electrode (RHE). Further applying this highly efficient NO3 – RR electrocatalyst as the cathode material, a novel Zn‐nitrate battery exhibits a power density of 3.25 mW cm –2 and a FE of 85.0% for NH3 production. This work enriches the application of Zn‐based batteries in the field of electrocatalysis and highlights the promise of bimetal phosphide for the NO3 – RR. Abstract : A Zn‐nitrate battery is reported to enable a "killing three birds with one stone" strategy for energy supply, ammonia production, and removal of pollutants with an iron doped nickel phosphide catalyst cathode. This battery system exhibits a power density of 3.25 mW cm −2 and a Faradaic efficiency of 85.0% for nitrate reduction to ammonia.